The Housing Bias Rethinking Land Use Laws for a Diverse New America - Boudreaux, P. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Arguing that our laws are skewed to benefit entrenched homeowners, at the expense of newcomers and lower-income households, this book advocates both for libertarian ideals and for social justice - an unusual and revealing combination.